Kinetic model of dynamic recrystallization of DP1000 steel for auto body structures. (14th April 2021) - Li, Hui; Rui, Feng; Xiao-li, Cui; Yao-kun, Pan; Xue-jie, Fu; Xuan, Ding
Abstract: Hot compression tests were performed in DP1000 steel under a temperature range of 950 ∼ 1150 °C with corresponding strain rate of 0.05 ∼ 10 s −1 to investigate the kinetic model of dynamic recrystallization (DRX) on a Gleeble 3800 thermal simulation test machine. The characteristic parameters such as critical stress/strain ( σ c / ε c ), peak stress/strain ( σ p / ε p ), maximum softening stress/strain ( σ m / ε m ) and steady-state stress/strain ( σ ss / ε ss ) were acquired according to the stress-strain data. The beginning of DRX was found from the inflection point of the cubic spline θ - σ curve. The Zahiri model was used to calculate the DRX percentage. The revised MZ DRX model based on multiple characteristic parameters was developed, and the prediction value had good agreement with the experimental results.